Exchange rate, GDP, and inflation in Tunisia: ARDL evidence of a u-shaped relationship - Soltani, Hassen (Asian Journal of Economic Modelling, 2025)
This paper investigates the nonlinear impact of the TND/USD exchange rate and real GDP on inflation in Tunisia over the period 1984–2023 using the autoregressive distributed lag (ARDL) bounds-testing approach. The analysis introduces quadratic terms to identify possible U-shaped or threshold relationships between the variables. Unit root tests confirm that all series are integrated of order one, I(1), and the bounds test indicates the existence of a long-run cointegration relationship (F-statistic ≈ 8.59). The estimated error-correction model suggests a rapid adjustment toward long-run equilibrium, as reflected by the significant and negative error-correction term (−1.64, p < 0.01). In the short run, inflation exhibits a partial exchange-rate pass-through, while in the long run, price dynamics are primarily influenced by real GDP growth. Quantitatively, the estimated turning points obtained from the quadratic specification occur at GDP ≈ 2.9 × 10¹⁰ (2015 USD) and EXCH ≈ 1.4 TND/USD, implying that inflation decreases up to these thresholds and rises beyond them. Overall, the results highlight the relevance of nonlinear monetary and exchange-rate policies that consider threshold effects to enhance price stability in the Tunisian economy.